EFFECT OF PROBIOTIC SUPPLEMENTATION ON LOW PROTEIN DIET ON BROILER PERFORMANCE - Suartika, I GB; Sumadi, IK; Bidura, IGNG (E-Journal Of Animal Science Udayana University, 2014)
This study was carried out to determine the effect of probiotics supplemented in low protein diets on performances of broiler aged 2-6 weeks. The design used was a completely randomized design (CRD) with three treatments and six replications. Each replication consisted of three broiler chickens aged two weeks with homogeneous body weight. The treatments were a standard ration containing 20% crude protein as a control diets (A), the ration with 18% crude protein content (B), and a diet with 18% crude protein content with a probiotic 0.20% Saccharomyces spp supplemented (C). Feed containing 2900kcal/kg metabolic energy and water were provided ad libitum. The results showed that the decrease of crude protein content rations of 2% units lower than the recommended standard rations (treatment B) were significantly reduced (P<0.05) on final body weight, body weight gains, and feed efficiency compared both with the control and treatmens C groups. In contrast, there were increased significantly different (P<0.05) on the amount of abdominal-fat. Supplementation of probiotic 0.20% Saccharomyces spp in the ration C were increased on body weight gains and feed efficiencies significantly different (P<0.05) compared with treatment B.  In contrast, there were decreased significantly (P<0.05) different on abdominal-fat and blood serum cholesterol contents of chicken.  It was concluded that supplementation of probiotic 0.20% Saccharomyces spp culture in ration with protein content 18 % resulting the same of broiler performance aged 2-6 weeks compared to the control. Supplementation of probiotic 0.20% Saccharomyces spp cultures in the ration can decrease abdominal fat and blood serum cholesterol contents of broiler aged 2-6 weeks.